Validation of Analytical Method for Quantification of Egg Cholesterol Using Reversed Phase-High Performance Liquid Chromatography-Multiwavelength Detector - Y. L. Maslukhah; D. N. Faridah; H. N. Lioe (Tropical Animal Science Journal, 2019)
In this research, analytical method of cholesterol content in eggs by Reversed Phase-High Performance Liquid Chromatography-Multiwavelength Detector (RP-HPLC-MWD) was validated. Our experiment validated the modified method of AOAC 994.10:2012 to get a more simple and efficient analytical method of cholesterol content. The sample was saponified using 10% KOH concentration for 15 min at 80 °C, then this analytical method was validated. RP-HPLC-MWD condition was at 100% MeOH as a mobile phase, flow rate of 1.0 mL/min, detection UV at 205 nm, cholesterol was detected at 10.38±0.13 min. As a result, the coefficients of determination for instrument and method linearities reached 0.9991 and 0.9912, respectively. The limits of detection and quantification of RP-HPLC-MWD instrument were found at 5 and 10 μg/mL, respectively, while the method-detection limit and quantification limit were 250 and 500 μg/g sample, respectively. Recovery values for the cholesterol analysis ranged from 98.62% to 112.26%, with a precision of 1.05%‒3.90%. Additionally, intralab reproducibility was known to reach 3.27%. This validated method can be applied for the analysis of cholesterol in various eggs available in the market.